ASESMEN FORMATIF BERBASIS APLIKASI QUIZIZZ UNTUK MENINGKATKAN PRESTASI BELAJAR ( Studi Pada Mata Pelajaran Kimia Kelas X MIPA di SMA Negeri 1 Pagar Alam) - Tenti Mariani; Wasidi Wasidi (UNIB Press, 2021)
The aims of this research is to describe the formative assessment based on the quizizz application to improve student learning achievement as well as to see its effectiveness on student achievement in Chemistry subject in class X MIPA at SMAN I Pagar Alam. This study design using classroom action research and continued with the experimental approach in the form of quasi exsperiment. The research subjects were students of class X MIPA 1 as the PTK class, X MIPA 2 as the Experiment class and X MIPA 3 as the control class. The data collection techniques used in the study were the observation sheets and student test results. Analysis of the data used is the average value (the mean) and the t-test test. The results of this study can be concluded that the assessment based on the application quizizz is effective in improving student achievement in chemistry subject in class X Mathematics and Natural Sciences students at SMA Negeri 1 Pagar Alam.